Talent detection in taekwondo: which factors are associated with the longitudinal competitive success? - Vieira Sarmet Moreira, P.; Fernandes Crozara, L.; Fagundes Goethel, M.; Vinhas de Paula, L.; Vieira, F. (Archives of Budo, 2014)
Background and Study Aim: Several morphological and functional characteristics are associated with the performance of taekwondo (TKD) adult athletes. However, we did not find any longitudinal study associating these features to the future performance of young athletes, and thereby, identifying the best variables to use in a battery of tests to talent detection. Therefore, the aim of this study is answer the question which factors are associated with the longitudinal competitive success of TKD young athletes over five competitive years (2008 to 2012). Material and Methods: Six taekwondo athletes (13.06 ± 1.07 years, 43.6 ± 6.6 kg, 157.9 ± 8.3 cm), who trained three to six hours per week, for more than three years, were assessed on 32 maturational indicators, of body composition, anthropometric and functional, using anthropometric techniques, dual energy x-ray absorptiometry, carpal radiography and contact platform. To determine the competitive ranking, the competitive results of athletes from 2008 to 2012 were analysed, and these values were correlated with the other 32 indicators for determining the Longitudinal Predictors of Performance in TKD (LPPT). Moreover, one of the athletes achieved results notably higher than the other, being medalled at Junior World Championships. Therefore, all variables were transformed into Z scores and all those in which this athlete presented superior performance in 1 Z score were considered as LPPT. Results: The athlete of reference (the first in Longitudinal Competitive Ranking 2008-2012) distinguished, in accordance with the criteria, in nineteen LPPT indicators. The ranking was correlated with 6 LPPT parameters, including one from the maturation group of indicators and five from the functional group. Conclusion: Our results allowed us to identify several factors that are related to longitudinal competitive success in taekwondo young athletes. These factors should be considered by coaches to the proper selection of training programs, as well as for the pre-selection of young talents in competitive taekwondo. However, these results apply only to the Portuguese taekwondo adolescent athletes, being of limited generalizability.